PENGEMBANGAN DAN PENERAPAN LOGIC MODEL PADA PROGRAM PEMBELAJARAN PENGUATAN VOCATIONAL LIFE SKILLS BERBASIS WIRAUSAHA - Jokebet Salundung (Universitas Negeri Yogyakarta, 2010)
This study is aimed at developing and applying the logic modelin planning, development, implementation, and evaluation of programs used in the design of the entrepreneurship-based model of the reinforced life skill vocational learning for home engineering students. The first year of the research and development phases is carried out by means of qualitative and quantitative procedures with observation, interviews, focus group discussions, questionnaires, document reviews, and the data are analyzed by the descriptive qualitative technique. This first year of the study (2009) begins with the analysis of situations, problems, and needs analysis, to obtain data which later are developed into the basis of strengthening the implementation of vocational learning life skills in the second year phases (2010). The results show that students and alumni experienced various problems and have not been competent in entrepreneurship so that they need strengthening vocational life skill-based entrepreneurship. All activities are planned, developed, and evaluated on the basis of system components in the form of the logic model